Quality of Charcoal Made from Gelam Wood (Melaleuca cajuputi) - Alpian Alpian; Tibertius A Prayitno; Gentur JP Sutapa; Budiadi Budiadi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
Gelam (Melaleuca cajuputi) dominantly found on tidal swamp areas of Central Kalimantan. The study was conducted to investigate the quality of charcoal from stem section based on the grow place, the location of A (flooded of the big tidal, peat thickness is 51-100 cm), location B (unflooded of the big tidal, peat thickness is 101-200 cm), and the stages of tree growth (saplings, poles, and trees). The parameters observed were yield, moisture content, volatile matter content, ash content, carbon content in bound, and calorific value. Charcoal from gelam generally meets the requirement of SNI 01-1683-1989, SNI 06-4369-1996, and Malaysia standards. The average value of the charcoal yield is 28.090-28.545%, the charcoal water content is 4.605-5.413%, the volatile matter content of charcoal is 30.286-34.635%, the ash content of charcoal is 1.840-2.386%, the bonded carbon content of charcoal is 58.37-62.46%, and the charcoal calorific value is 6937.43-7530.09 cal g-1.Key words: biomass energy, calorific value, charcoal, Melaleuca cajuputi